Biopsychosocial experiences and coping strategies of elderly ESRD patients: a qualitative study to inform the development of more holistic and person-centred health services in Singapore - Emeline Han; Farah Shiraz; Victoria Haldane; Joel Jun Kai Koh; Rina Yu Chin Quek; Semra Ozdemir; Eric Andrew Finkelstein; Tazeen Hasan Jafar; Hui-Lin Choong; Sheryl Gan; Lydia W. W. Lim; Helena Legido-Quigley (BMC, 2019)
Abstract Background As the incidence and prevalence rates of end stage renal disease (ESRD) rise globally, a disproportionate increase has been observed in the elderly population. Singapore has the fifth highest incidence of treated ESRD worldwide, with the upward trend of ESRD being most apparent among those aged 70 years and older. Although it is well-documented that ESRD patients suffer an impaired quality of life compared to the general population, there is limited research focusing on the unique experiences and needs of elderly ESRD patients in Asian populations. To address the knowledge gap, this study seeks to explore the impact of ESRD and dialysis on the quality of life of elderly (≥70 years old) ESRD patients in Singapore and examine the coping strategies utilised by these patients. Methods This qualitative study involved semi-structured, in-depth interviews with 7 peritoneal dialysis patients, 5 haemodialysis patients, 4 patients on non-dialysis supportive care and 7 caregivers in Singapore. Interviews were conducted in English, Chinese, and Malay and fully transcribed. QSR NVivo 11 software was used for analysis. Results Participants reported that ESRD and dialysis had an impact on three highly interconnected areas of their quality of life: (a) biological/physical (general symptoms, neuromuscular problems, skin problems and poor sleep quality); (b) psychological (depressive symptoms, anxiety and fears, stress and negative self-perceptions); and (c) social (increased dependence on family and loss of social life). There were four key strategies that participants used to cope with these biopsychosocial challenges: (a) family support (financial, practical and emotional support); (b) religious/spiritual support (experiencing gratitude/contentment, the power of prayer and belonging to a faith community); (c) avoidance (cognitive avoidance and distraction techniques); and (d) acceptance (positive thinking and problem solving). Conclusions This study has provided insights into the biopsychosocial impact of ESRD and dialysis, as well as cultural and religious factors that shape the experiences and coping mechanisms of elderly ESRD patients and caregivers in Singapore, which can be used to further the development and implementation of more holistic and person-centred services to help each patient achieve a better quality of life.